Assessment of Biogenic Elements and Heavy Metals Content in the Topsoil of the Coastal Islands of Antarctic Peninsula - S. G. Korsun (Ukrainian Antarctic Journal, 2005)
It were revealed the wide limits of variation of the biogenic elements and heavy metals content in the topsoil of the coastal islands of Antarctic Peninsula. The chemical elements accumulation is partly explained by existence of geochemical barriers of physical and chemical character. To explain the occurrence of geochemical areas in the certain territory of Antarctica differing in a degree of biogenic elements and heavy metals accumulation, monitoring on a landscape-geochemical basis is required.